Protocol for a pragmatic randomised controlled trial of Body Brain Life—General Practice and a Lifestyle Modification Programme to decrease dementia risk exposure in a primary care setting. Issue 3 (17th March 2018) - Kim, Sarang; McMaster, Mitchell; Torres, Susan; Cox, Kay L; Lautenschlager, Nicola; Rebok, George W; Pond, Dimity; D'Este, Catherine; McRae, Ian; Cherbuin, Nicolas; Anstey, Kaarin J
Abstract : Introduction: It has been estimated that a 10%–25% reduction in seven key risk factors could potentially prevent 1.1–3.0 million Alzheimer's disease cases globally. In addition, as dementia is preceded by more subtle cognitive deficits which have substantial social and economic impact, effective preventative interventions would likely have more extensive benefits. The current study evaluates in primary care a multidomain risk-reduction intervention targeting adults with high risk of developing dementia. Methods and analysis: A randomised controlled trial (RCT) is being conducted to evaluate three intervention programmes using a pragmatic approach suitable to the clinic: (1) a 12-week online and face-to-face dementia risk-reduction intervention (Body Brain Life—General Practice (BBL-GP)); (2) a 6-week face-to-face group lifestyle modification programme (LMP); and (3) a 12-week email-only programme providing general health information. We aim to recruit 240 participants, aged 18 and over, to undergo a comprehensive cognitive and physical assessment at baseline and follow-ups (postintervention, 18, 36 and 62 weeks). The primary outcome is dementia risk measured with the modified version of the Australian National University—Alzheimer's Disease Risk Index Short Form. Secondary outcomes are cognitive function measured with Trails A and B, and the Digit Symbol Modalities Test; physical activity with moderate-vigorous physical activity and the International Physical Activity Questionnaire; depression with the Centre for Epidemiological Studies Depression; cost evaluation with the 12-item Short Form Health Survey, Framingham Coronary Heart Disease Risk Score and Australian Type 2 Diabetes Risk Assessment Tool; diet quality with the Australian Recommended Food Score; and sleep quality with the Pittsburgh Sleep Quality Index. Ethics and dissemination: This RCT is a novel pragmatic intervention applied in a primary care setting to reduce the dementia risk exposure in adults at high risk. If successful, BBL-GP and LMP will provide a versatile, evidence-based package that can be easily and quickly rolled out to other primary care settings and which can be scaled up at relatively low cost compared with other strategies involving intensive interventions. Trial registration number: ACTRN12616000868482